A TetR-Family Protein (CAETHG_0459) Activates Transcription From a New Promoter Motif Associated With Essential Genes for Autotrophic Growth in Acetogens - de Souza Pinto Lemgruber, Renato; Valgepea, Kaspar; Gonzalez Garcia, Ricardo Axayacatl; de Bakker, Christopher; Palfreyman, Robin William; Tappel, Ryan; Köpke, Michael; Simpson, Séan Dennis; Nielsen, Lars Keld; Marcellin, Esteban (Frontiers in Microbiology, 2019)
Acetogens can fix carbon (CO or CO2) into acetyl-CoA via the Wood-Ljungdahl pathway (WLP). Acetogens are attractive cell factories for fuels and chemicals production from waste feedstocks. Although most biochemical characteristics of the WLP are understood, and systems-level characterisation of acetogen metabolism has recently improved, many transcriptional features of promoter motifs and transcriptional regulators are still unknown. Here, we use differential RNA-sequencing to identify a previously undescribed promoter motif associated with essential genes for autotrophic growth of Clostridium autoethanogenum. Binding of the RNA polymerase to the new promoter motif using DNA-binding protein assay and mass spectrometry enabled the discovery of four candidates to potentially function directly in control of transcription of the WLP and other key genes of C1 fixation metabolism. In vivo experiments showed that a TetR-family transcriptional regulator (CAETHG_0459) and the housekeeping sigma factor (σA) activate expression of a reporter protein (GFP) from a fusion vector in E. coli. A protein-protein interaction assay with the RNA polymerase (RNAP) shows that CAETHG_0459 directly binds to RNAP to positively regulate the new promoter motif transcription. Together, the data presented here advance the fundamental understanding of transcriptional regulation of C1 fixation in acetogens and provide a strategy to improve the performance of gas-fermenting bacteria by genetic engineering.